2015
DOI: 10.1111/jmwh.12362
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Certified Nurse‐Midwife Scope of Practice: Change in the Professional Practice Index, 2000 to 2015

Abstract: The CNMPPI can be used to document changes in practice authority of CNMs. The increase in state CNMPPI scores and decrease in variance across states can be interpreted as indicating growth of professional authority and increasing consensus regarding the CNM role. The scoring system needs to be updated to reflect the current health systems environment and to include certified midwives and other midwives meeting the International Confederation of Midwives definition of a midwife. Applications of the CNMPPI to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 7 publications
4
31
0
1
Order By: Relevance
“…Since 2000, the professional practice environment of CNMs in the U.S.A has been regularly examined regarding legal status, reimbursement and prescriptive authority. Texas scores increased 21.3% from 2000–2015 with smallest gains made in legal status and prescriptive authority; greatest increase was in reimbursement (Beal et al., ) demonstrating but modest improvement in midwifery practice autonomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since 2000, the professional practice environment of CNMs in the U.S.A has been regularly examined regarding legal status, reimbursement and prescriptive authority. Texas scores increased 21.3% from 2000–2015 with smallest gains made in legal status and prescriptive authority; greatest increase was in reimbursement (Beal et al., ) demonstrating but modest improvement in midwifery practice autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…greatest increase was in reimbursement (Beal et al, 2015) demonstrating but modest improvement in midwifery practice autonomy.…”
Section: Legislative Issues and Practice Barriersmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, previous research has found that autonomous practice for CNMs is associated with a greater supply of CNMs, and with a greater likelihood of births being attended by midwives . An examination of the nurse‐midwifery environment across all states in 2015 found that New York CNMs were second out of the 50 states and the District of Columbia in professional authority . Other states may consider whether their regulatory environments may influence access to and value derived from midwifery care.…”
Section: Discussionmentioning
confidence: 99%